EFEKTIVITAS SISTEM INFORMASI PEMERINTAHAN DAERAH DALAM MENGOPTIMALKAN PENGELOLAAN KEUANGAN DI BADAN PENGELOLAAN KEUANGAN DAN ADET DAERAH KABUPATEN BOJONEGORO - Sekar Damayanti; Tukiman (Halu Oleo University, 2025)
This study aims to analyse the effectiveness of SIPD implementation in optimising financial management at the Regional Financial and Asset Management Agency (BPKAD) of Bojonegoro Regency. The research method employed is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. Data analysis uses the Miles interactive model with effectiveness evaluation based on the DeLone and McLean (2003) model. The research results show that of the six evaluated indicators, only service quality was assessed as effective, while the other five indicators were ineffective. System quality faced constraints, including an uncomfortable interface and limited features. Information quality showed significant differences across work divisions, with treasury and accounting divisions experiencing information limitations. SIPD usage levels were very high but accompanied by operational constraints. User satisfaction varied, with the budget division showing high satisfaction while the treasury and accounting divisions experienced dissatisfaction. Implementation impact demonstrated regulatory compliance but generated a high operational burden. Therefore, it can be concluded that the Regional Government System at the Regional Financial and Asset Management Agency has not been effective in optimising regional financial management.